Innovative methods of marine ecosystem restoration - Goreau,Thomas J. and Trench,Robert Kent (CRC Press, 2013)
"Presenting, for the first time, data showing the dramatic results of these methods, this book presents innovative new technologies for restoring the most productive ecosystems on both land and sea while maintaining high biodiversity. These technologies are a quantum leap beyond current methods in effectiveness at restoring the biological productivity and the ecological, environmental, and economic services of ecosystems that maintain global atmospheric composition, climate, agriculture, forestry, fisheries, beaches, and fresh water supplies. The text serves as a guide to maintaining ecosystem functioning under conditions that would otherwise kill most of the key organisms living in them"--